Treatment of Cystitis by Hungarian General Practitioners: A Prospective Observational Study - Benko, Ria; Matuz, Maria; Juhasz, Zoltan; Bognar, Julia; Bordas, Reka; Soos, Gyongyver; Hajdu, Edit; Peto, Zoltan (Frontiers in Pharmacology, 2019)
Background: Lower urinary tract infections (LUTIs) are amongst the most common community acquired infections with frequent antibiotic prescribing. Objectives: To assess empiric antibiotic choice in different types of lower urinary tract infections. We also aimed to identify determinants of fluoroquinolone prescribing, as well as to determine the rate of short antibiotic courses. The frequencies of executing laboratory tests and recommending analgesics/anti-inflammatory drugs were also assessed. Methods: A prospective observational study was performed in 19 different Hungarian primary care practices. Participating general practitioners (GPs) filled out data sheets for each patient with a suspected urinary tract infection. Details of drug use were evaluated. Comparison of different LUTI groups were made by descriptive statistics and univariate analysis. Possible determinants of fluoroquinolone prescribing were assessed by logistic regression. Results: Data sheets of 372 patients were analyzed. The majority of patients (68.82%) had acute uncomplicated cystitis. While antibiotics were prescribed for almost every patient (uncomplicated cases: 92.58%, complicated cases: 94.83%), analgesics/anti-inflammatory drugs were recommended at a rate of 7.81% in uncomplicated, and 13.79% in complicated cystitis cases. Ciprofloxacin was the most commonly prescribed antibacterial agent in both types of cystitis. Short-term antibiotic therapy was prescribed in one third of relevant cases. Logistic regression found a weak association between fluoroquinolone use and patient’s age and presence of complicating factors. Conclusions: Many aspects of suboptimal cystitis management were identified (e.g. unnecessarily broad spectra agents, too long antibiotic courses). In this study, patient characteristics has weakly influenced fluoroquinolone prescribing. Based on these results there is considerable room for improvement in primary care antibiotic therapy of cystitis in Hungary.